Exploring the Impact of Early STEM Education on Science and Visual Literacy - Moleboheng Ramulumo (Journal of Education in Science, Environment and Health)
Early STEM (Science, Technology, Engineering, and Mathematics) education plays a pivotal role in shaping children's science and visual literacy skills. However, in South Africa, there are notable challenges such as delayed initiation of science education and inadequate emphasis on visual literacy. This study aims to investigate the influence of early STEM education on science and visual literacy in South African educational contexts. Drawing upon the post-positivist paradigm and Mayer's cognitive theory of multimedia learning, this research employed a mixed-method approach combining quantitative and qualitative analyses, integrating autoethnography to engage with lived experiences during my master's and doctoral studies. The findings suggest that children exposed to STEM education demonstrate higher levels of science and visual literacy. These findings have implications for curriculum design and educational practice, urging stakeholders to integrate STEM principles early in children's educational journey and to prioritize visual literacy to enhance communication and comprehension of scientific concepts. Recommendations are provided for educational institutions and policymakers to facilitate the implementation of effective strategies addressing these challenges and fostering a generation of learners equipped with essential skills for success in the modern world.